The benefits of progesterone therapy in imminent abortion (Medical Journal of Indonesia, 2005)
The causes of imminent abortion are multi-factorial. The biggest causal factor is the low level of serum progesterone level. The lowest critical level of serum progesterone for survivability of pregnancy is 10 ng/ml. Eighty percent of patients experiencing abortion showed that their progesterone level was < 10 ng/ml. Patients who realized that their pregnancy would experience hemorrhage generally would suffer from depression. Stress was one of the factors responsible for the occurence of abortion. Administration of natural progesterone substitution (not progestogen) accelerates the disappearance of uterine contractions, and speeds up the stoppage of bleeding. In addition, progesterone has the effect of anti-anxiety. Adminstration of oral progesterone would result in metabolism in the intestine and liver, such that physiological level of serum progesterone could not be reached, while administration of suppositoria progesterone would result in physiological level of serum, such that it was effective to prevent imminent abortion. (Med J Indones 2005; 14:258-62)